NON-INVASIVE DIAGNOSTIC METHODS FOR ABDOMINAL INJURIES (International Conference on Modern Science and Scientific Studies, 2025)
The literary review presents current trends in the use of ultrasound (ultrasound) and multislice computed tomography (MSCT) in the diagnosis of closed abdominal injuries. During discussing the issues of sonography, special emphasis is placed on publications devoted to assessing the informativeness of the so-called FAST-protocol ("Focused assessment with sonography in trauma"), which is included in the clinical recommendations of ATLS (Advanced Trauma Life Support), as a mandatory initial diagnostic study of patients with severe trauma. It is also shown that MSCT is currently considered the gold standard in the diagnosis of abdominal injuries.